Recombinant Virus Vaccination against “Self” Antigens Using Anchor-fixed Immunogens - Irvine, Kari R. (1999)
To study the induction of anti-“self” CD8(+) T-cell reactivity against the tumor antigen gp100, we used a mouse transgenic for a chimeric HLA-A*0201/H-2 K(b) molecule (A2/K(b)). We immunized the mice with a recombinant vaccinia virus encoding a form of gp100 that had been modified at position 210 (from a threonine to a methionine) to increase epitope binding to the restricting class I molecule. Immunogens containing the “anchor-fixed” modification elicited anti-self CD8(+) T cells specific for the wild-type gp100(209–217) peptide pulsed onto target cells. More important, these cells specifically recognized the naturally presented epitope on the surface of an A2/K(b)-expressing murine melanoma, B16. These data indicate that anchor-fixing epitopes could enhance the function of recombinant virus-based immunogens.